Case report: Malaria and Thrombocytopenia at Pimping Community Health Center, North Kalimantan, an Endemic Area in Indonesia - Ni Luh Putu Winda Alpiniawati (Asian Journal of Social and Humanities, 2023)
Thrombocytopenia is one of the most frequent side effects of both Plasmodium vivax and Plasmodium falciparum malaria, despite the fact that it is not a sign of severe malaria. However, few studies said that thrombocytopenia would early recognition of severe malaria. Moreover, thrombocytes play a significant part in inflammatory response during malaria.   In these cases, present malaria falciparum and vivax with thrombocytopenia without bleeding and any severe malaria. The case diagnosis with a rapid diagnostic test of malaria and peripheral blood examination.